Approximation Properties of a Gradient Recovery Operator Using a Biorthogonal System. (3rd February 2015) - Lamichhane, Bishnu P.; McNeilly, Adam
Abstract : A gradient recovery operator based on projecting the discrete gradient onto the standard finite element space is considered. We use an oblique projection, where the test and trial spaces are different, and the bases of these two spaces form a biorthogonal system. Biorthogonality allows efficient computation of the recovery operator. We analyze the approximation properties of the gradient recovery operator. Numerical results are presented in the two-dimensional case.